ORIENTASI PEMILIH PEREMPUAN TERHADAP PASANGAN CALON PEREMPUAN DALAM PEMILIHAN KEPALA DAERAH KABUPATEN SIAK TAHUN 2020 (STUDI KASUS KECAMATAN DAYUN) - Chairani, Maydisha Wita; ', Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
The involvement of women in the public and political arena is an important step to rebuild economic, political and social conditions to achieve equality for women and men in obtaining opportunities and achieving progress. The participation of women voters in this case is very necessary to make the regional head elections a success by channeling their voting rights. Political orientation can also be interpreted as political culture, namely there are many definitions of political culture, but in principle what is meant by this term is nothing other than the typical orientation attitude of citizens. state towards the political system and its various parts, and attitudes towards the role of citizens in that system: 1. Cognitive Orientation, 2. Affective Orientation, 3. Evaluative Orientation. This research uses qualitative research methods, with the reason that it is empirical. The problems observed are more appropriate using this method. The results of the research show that there are several factors that influence female voters in determining their choice to elect a regional head, ranging from social, economic position, the proximity of the leader candidate to the community, to external factors or influence from other people, such as influence from husbands, family and those closest to them. , because it has become a culture and belief that the leader is a man. Keywords: Political Orientation, Orientation of Women Voters